Doped halide solid electrolyte and preparation method thereof, all-solid-state battery and electrical device
By using doped halide solid electrolytes in all-solid-state batteries, the migration and content of lithium ions are regulated, and the ion transfer difficulty caused by solid interface contact is solved, and the electrochemical performance and stability of the battery are improved.
Patent Information
- Application Number
- CN202410464797.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-17
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-04-17
AI Technical Summary
The contact between the solid interface between the positive electrode and the electrolyte layer in an all-solid state battery causes difficulty in ion transmission, resulting in high internal resistance and affecting electrochemical performance.
Doped halide solid electrolyte, its general formula is Li6-ma-czAa+mxBb+myCc+zX6, through the introduction of B ions and C ions, the migration of lithium ions is regulated, the lithium vacancies are increased, the ion conductivity is improved, and the ion is regulated by the regulation. The numerical value of m controls the lithium content and keeps the phase state and spatial group unchanged.
It significantly improves the ionic conductivity of all-solid state batteries, improves solid interface contact, and improves electrochemical performance, including high first-time Coulomb efficiency and good cycling stability.
Smart Images

Figure CN118073640B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a doped halide solid electrolyte, a preparation method thereof, an all-solid-state battery, and an electrical device. Background Art
[0002] Compared with liquid batteries, all-solid-state batteries use solid electrolytes and are not prone to combustion, explosion, etc., so they have high reliability. At present, the main obstacle on the commercialization path of all-solid-state batteries is that the contact between the positive electrode and the electrolyte layer is a solid-solid interface contact, and ion transport is relatively difficult, resulting in a high internal resistance of the all-solid-state battery and affecting its electrochemical performance. Summary of the Invention
[0003] The present application provides a doped halide solid electrolyte, a preparation method thereof, an all-solid-state battery, and an electrical device. The doped halide solid electrolyte has better ionic conductivity performance compared with the original matrix material.
[0004] In a first aspect, the present application provides a doped halide solid electrolyte. The general formula of the doped halide solid electrolyte is Li 6-ma-cz A a+ mx B b+ my C c+ z X 6 , where a is the valence of A ions, b is the valence of B ions, c is the valence of C ions, a is 3 or 4, b is 4, 5 or 6, c is 2, 3, 4, 5 or 6, ax + by = a, b > a, x > y > 0, 0 ≤ z < 0.5, 0 < m < 1.5, mx + my + z < 1; A includes one or more of Ga, In, Sc, Y, lanthanide metals, Sb, Bi, Ti, Zr, Hf; B includes one or more of Ti, Zr, Hf, V, Nb, Ta, Mo, W; C includes one or more of Mg, Ca, Sr, Ba, Ga, In, Sc, Y, lanthanide metals, Sb, Bi, Ti, Zr, Hf, V, Nb, Ta, Mo, W, and A, B, and C are different; X includes one or more of halogens.
[0005] ax+by=a, b>a, after the introduction of B ions, the total charge number provided by A ions and B ions is consistent with the charge number provided by A ions alone before modification, so that when a higher valence B ion is added, the total number of occupancy of A ions and B ions is less than 1, that is, more A vacancies are generated, which can reduce the obstruction of Coulomb repulsion for the migration of lithium ions and achieve the improvement of ionic conductivity. The addition of C ions can regulate the lithium ion content and induce more lithium vacancies. By adjusting the content of C ions, the doped halide solid electrolyte can have the same phase and space group as the original matrix material. By adjusting the value of m, the lithium content of the doped halide solid electrolyte can be adjusted to achieve regulation between the lithium-poor state (i.e., high lithium ion vacancy number) and the lithium-rich state (i.e., high lithium ion concentration). Therefore, the doped halide solid electrolyte provided in the embodiment of the present application has better ionic conductivity performance than the original matrix material, which is conducive to its practical application in all-solid-state batteries.
[0006] In some embodiments, <z≤0.2。
[0007] In some embodiments, a is 4, b is 5, and c is 2, 3, 4, or 5.
[0008] In some embodiments, 0.5≤m≤1.25.
[0009] In some embodiments, 0.5≤mx<1.
[0010] In some embodiments, the ionic radius of the C ion is greater than the ionic radius of the A ion, and the ionic radius of the C ion is greater than the ionic radius of the B ion. When the ionic radius of the doped C ion is greater than the ionic radius of the A ion and greater than the ionic radius of the B ion, the C ion can widen the distance between the cation layers and further weaken the resistance to lithium ion migration.
[0011] In some embodiments, A includes one or more of In, Y, Zr, and lanthanide metals.
[0012] In some embodiments, B includes one or more of Zr, Hf, Nb, and Ta.
[0013] In some embodiments, C includes one or more of Ca, In, La, Ce, Pr, Nd, Sm, Eu, Gd, Zr, Hf, Nb, Ta, and Mo, and A, B, and C are different.
[0014] In some embodiments, X includes one or more of Cl, Br, and I.
[0015] In some embodiments, the doped halide solid electrolyte is in any one of a glass phase, a glass-ceramic phase, and a crystalline phase.
[0016] In some embodiments, the volume distribution particle size Dv50 of the doped halide solid electrolyte is 0.5 μm - 10 μm.
[0017] In some embodiments, the ionic conductivity of the doped halide solid electrolyte at 25 °C is 0.5 mS / cm - 15 mS / cm.
[0018] In a second aspect, the present application provides a method for preparing a doped halide solid electrolyte, comprising the following steps: uniformly mixing a halide of element Li, a halide of element A, a halide of element B, and optionally a halide of element C in proportion, then grinding under a protective gas atmosphere, and then annealing the ground material under a protective gas atmosphere to obtain a doped halide solid electrolyte. The general formula of the doped halide solid electrolyte is Li 6-ma-cz A a+ mx B b+ my C c+ z X 6 , where a is the valence of A ions, b is the valence of B ions, c is the valence of C ions, a is 3 or 4, b is 4, 5 or 6, c is 2, 3, 4, 5 or 6, ax + by = a, b > a, x > y > 0, 0 ≤ z < 0.5, 0 < m < 1.5, mx + my + z < 1; A includes one or more of Ga, In, Sc, Y, lanthanide metals, Sb, Bi, Ti, Zr, Hf; B includes one or more of Ti, Zr, Hf, V, Nb, Ta, Mo, W; C includes one or more of Mg, Ca, Sr, Ba, Ga, In, Sc, Y, lanthanide metals, Sb, Bi, Ti, Zr, Hf, V, Nb, Ta, Mo, W, and A, B, and C are different; X includes one or more of halogens.
[0019] In some embodiments, the rotation speed of grinding is 300 rpm - 600 rpm, and optionally 400 rpm - 550 rpm.
[0020] In some embodiments, the grinding time is 6 h - 72 h, and optionally 12 h - 48 h.
[0021] In some embodiments, the annealing temperature is 100 °C - 300 °C, and optionally 100 °C - 200 °C.
[0022] In some embodiments, the annealing time is 2 h - 24 h, and optionally 5 h - 12 h.
[0023] In a third aspect, the present application provides an all-solid-state battery, comprising a positive electrode, wherein the positive electrode comprises a positive electrode active material and a doped halide solid electrolyte according to the first aspect of the present application or a doped halide solid electrolyte prepared by the preparation method of the second aspect of the present application.
[0024] Compared with the original matrix material, the doped halide solid electrolyte has better ionic conductivity performance and can improve the problem of poor solid-solid interface contact, which is beneficial to the electrochemical performance of all-solid-state batteries, making them have high first coulombic efficiency and good cycle stability.
[0025] In some embodiments, the mass ratio of the positive electrode active material to the doped halide solid electrolyte is 90:10 to 70:30.
[0026] In some embodiments, the positive electrode active material includes one or more of lithium cobalt oxide and its modified materials, lithium iron phosphate and its modified materials, lithium iron manganese phosphate and its modified materials, lithium nickel cobalt manganese oxide and its modified materials, lithium nickel cobalt aluminum oxide and its modified materials, lithium nickel oxide and its modified materials, lithium manganese oxide and its modified materials, lithium titanate, sulfur, selenium, and tellurium.
[0027] In some embodiments, the all-solid-state battery also includes a negative electrode and an electrolyte layer, the electrolyte layer is located between the positive electrode and the negative electrode, and the negative electrode includes one or more of graphite, graphene, carbon nanotubes, intermediate phase microcarbon beads, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, metal oxides, metallic lithium, lithium alloys, and lithium composite materials.
[0028] In a fourth aspect, the present application provides an electrical device comprising the all-solid-state battery of the third aspect of the present application.
[0029] The electrical device of the present application includes the all-solid-state battery provided in the present application, and thus has at least the same advantages as the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0031] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.
[0032] Figure 2 It is an exploded schematic diagram of an embodiment of a battery cell of the present application.
[0033] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.
[0034] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0035] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0036] Figure 6 It is a schematic diagram of an embodiment of an electrical device including the all-solid-state battery of the present application as a power source.
[0037] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION
[0038] Hereinafter, the doped halide solid electrolyte and its preparation method, all-solid-state battery and electric device of the present application are described in detail with appropriate reference to the accompanying drawings, and the embodiments are specifically disclosed. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0039] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0040] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0041] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0042] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0043] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are generally understood by those skilled in the art.
[0044] Unless otherwise specified, the values of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.
[0045] The all-solid-state battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the all-solid-state battery mentioned in the present application may include a battery cell, a battery module or a battery pack.
[0046] A battery cell is the smallest unit of an all-solid-state battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular, or in other shapes, etc., which is not limited in the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.
[0047] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the all-solid-state battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the all-solid-state battery may be a battery pack, which includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.
[0048] In some embodiments, the all-solid-state battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.
[0049] The battery cell includes an electrode assembly and an outer package. The outer package can be used to encapsulate the electrode assembly. The outer package can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of aluminum-plastic film, polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0050] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to needs.
[0051] In some embodiments, battery cells can be assembled into a battery module. The number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0052] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0053] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0054] like Figure 4 and Figure 5 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.
[0055] Sulfide solid electrolytes are considered to be key materials for the industrialization of all-solid-state batteries due to their advantages such as high ionic conductivity and low Young's modulus. However, sulfide solid electrolytes have problems such as poor positive electrode stability, high cost, and easy decomposition and release of toxic gases. Therefore, it is necessary to find other suitable solid electrolytes for the positive electrode besides sulfide solid electrolytes. The physical and chemical properties of halide solid electrolytes are similar to those of sulfide solid electrolytes, and they also have a lower Young's modulus, so that they can form a good interface contact with the electrode material. In addition, due to the characteristics of the anions of halide solid electrolytes, they have a far superior positive electrode stability than sulfide solid electrolytes, so that the first coulombic efficiency and cycle stability of all-solid-state batteries can be improved simultaneously. However, the ionic conductivity of halide solid electrolytes is generally not high, which limits their application in the industrialization of all-solid-state batteries. At present, the industry is still exploring modification strategies for halide solid electrolytes in order to significantly improve their ionic conductivity.
[0056] Based on this, an embodiment of the present application provides a doped halide solid electrolyte, which has better ionic conductivity than an undoped halide solid electrolyte matrix material. When used in the positive electrode of an all-solid-state battery, it can increase the gram capacity of the positive electrode active material and improve the cycle performance of the all-solid-state battery.
[0057] The general formula of the doped halide solid electrolyte provided in the embodiment of the present application is Li 6-ma-cz Aa+ mx B b+ my C c+ z X 6 .
[0058] a is the valence of ion A, b is the valence of ion B, c is the valence of ion C, a is 3 or 4, b is 4, 5 or 6, c is 2, 3, 4, 5 or 6, ax+by=a, b>a, x>y>0, 0≤z<0.5, 0 <m<1.5,mx+my+z<1。
[0059] A includes one or more of Ga, In, Sc, Y, lanthanide metals, Sb, Bi, Ti, Zr, and Hf, B includes one or more of Ti, Zr, Hf, V, Nb, Ta, Mo, and W, C includes one or more of Mg, Ca, Sr, Ba, Ga, In, Sc, Y, lanthanide metals, Sb, Bi, Ti, Zr, Hf, V, Nb, Ta, Mo, and W, and A, B, and C are different. X includes one or more of halogens.
[0060] x>y>0, the doped halide solid electrolyte provided in the embodiment of the present application is based on the halide solid electrolyte matrix material Li 6-a A a+ X 6 0≤z<0.5, which means that C ions can be doped into the doped halide solid electrolyte or not.
[0061] ax+by=a, b>a. After the introduction of B ions, the total charge number provided by A ions and B ions is consistent with the charge number provided by A ions alone before modification. Therefore, when higher-valence B ions are doped, the total occupancy number of A ions and B ions is less than 1, that is, more A vacancies are generated, thereby reducing the Coulomb repulsion that hinders the migration of lithium ions and improving the ionic conductivity.
[0062] In addition, whether C ions are doped or not, it is necessary to satisfy mx+my+z<1, thereby generating more A vacancies, reducing the Coulomb repulsion for the migration of lithium ions, and improving the ionic conductivity. The addition of C ions can regulate the lithium ion content and induce more lithium vacancies. In addition, by adjusting the content of C ions, the doped halide solid electrolyte can have the same phase and space group as the original matrix material.
[0063] m is a coefficient for adjusting the lithium - poor state and lithium - rich state. 0 < m < 1.5. By adjusting the value of m, the lithium content of the doped halide solid electrolyte can be adjusted to achieve the regulation between the lithium - poor state (i.e., high lithium - ion vacancy number) and the lithium - rich state (i.e., high lithium - ion concentration). The lithium - ion vacancy number and the lithium - ion concentration are two important factors affecting the ionic conductivity of the doped halide solid electrolyte, but these two factors are antagonistic to each other. Different all - solid - state batteries have different requirements for the doped halide solid electrolyte. Therefore, by adjusting the value of m, the doped halide solid electrolyte can be switched between the lithium - poor state and the lithium - rich state, its structural design is more flexible, and the battery application is more extensive.
[0064] Therefore, the doped halide solid electrolyte provided by the embodiments of the present application has better ionic conductivity performance compared with the original matrix material, which is beneficial to realizing its practical application in all - solid - state batteries.
[0065] In some embodiments, optionally, the lanthanide metal may include one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu.
[0066] In some embodiments, optionally, 0.5 ≤ m ≤ 1.25.
[0067] In some embodiments, optionally, 0 ≤ z ≤ 0.2. More optionally, 0 < z ≤ 0.2.
[0068] In some embodiments, optionally, a is 4, b is 5, c is 2, 3, 4 or 5; or, a is 3, b is 4 or 5, c is 2, 3, 4 or 5.
[0069] In some embodiments, optionally, 0.5 ≤ mx < 1. More optionally, 0.6 ≤ mx < 1, 0.65 ≤ mx < 1, 0.7 ≤ mx < 1, 0.75 ≤ mx < 1, 0.8 ≤ mx < 1.
[0070] In some embodiments, optionally, the ionic radius of the C ion is greater than the ionic radius of the A ion, and the ionic radius of the C ion is greater than the ionic radius of the B ion.
[0071] When the ionic radius of the incorporated C ion is greater than the ionic radius of the A ion and greater than the ionic radius of the B ion, the C ion can play a role in broadening the cation layer spacing and further weakening the lithium - ion migration resistance, thereby enabling the doped halide solid electrolyte to have better ionic conductivity performance.
[0072] In some embodiments, optionally, A may include one or more of In, Y, Zr, lanthanide metals.
[0073] In some embodiments, B may optionally include one or more of Zr, Hf, Nb, and Ta.
[0074] In some embodiments, optionally, C may include one or more of Ca, In, La, Ce, Pr, Nd, Sm, Eu, Gd, Zr, Hf, Nb, Ta, and Mo, and A, B, and C are different.
[0075] X includes one or more of halogens. In some embodiments, X may optionally include one or more of F, Cl, Br, and I. More optionally, X may include one or more of Cl, Br, and I.
[0076] For example, X 6 Can be F 6 , Cl 6 Br 6 ,I 6 、F x Cl 6-x , Cl x Br 6-x , Cl x I 6-x Any of the above, where x is greater than 0 and less than 6.
[0077] The doped halide solid electrolyte may be in any of a glass phase, a glass-ceramic phase, and a crystalline phase.
[0078] In some embodiments, the volume distribution particle size Dv50 of the doped halide solid electrolyte may be 0.5 μm-10 μm.
[0079] In some embodiments, the ionic conductivity of the doped halide solid electrolyte at 25° C. may be 0.5 mS / cm-15 mS / cm. 6-a A a+ X 6 The ionic conductivity of doped halide solid electrolytes varies with the type and content of doped elements (such as B, C), the value of m, etc.
[0080] The embodiment of the present application also provides a method for preparing the above-mentioned doped halide solid electrolyte.
[0081] The preparation method includes the following steps: proportionally and uniformly mix the halide of element Li, the halide of element A, the halide of element B, and optionally the halide of element C, then grind under a protective gas atmosphere, and then anneal the ground material under a protective gas atmosphere to obtain a doped halide solid electrolyte. The molar ratio of element Li, element A, element B, and element C is (6 - ma - cz) : mx : my : z, where a is the valence of A ion, b is the valence of B ion, c is the valence of C ion, a is 3 or 4, b is 4, 5 or 6, c is 2, 3, 4, 5 or 6, ax + by = a, b > a, x > y > 0, 0 ≤ z < 0.5, 0 < m < 1.5, and mx + my + z < 1. A includes one or more of Ga, In, Sc, Y, lanthanide metals, Sb, Bi, Ti, Zr, Hf; B includes one or more of Ti, Zr, Hf, V, Nb, Ta, Mo, W; C includes one or more of Mg, Ca, Sr, Ba, Ga, In, Sc, Y, lanthanide metals, Sb, Bi, Ti, Zr, Hf, V, Nb, Ta, Mo, W, and A, B, and C are different. The general formula of the doped halide solid electrolyte is Li 6-ma-cz A a+ mx B b+ my C c+ z X 6 . X includes one or more of halogens.
[0082] When preparing the doped halide solid electrolyte, adjust ax + by = a, b > a. After introducing B ions, the total charge provided by A ions and B ions is the same as the charge provided by A ions alone before modification. Thus, when higher-valence B ions are incorporated, the total occupancy of A ions and B ions is less than 1, that is, more A vacancies are generated, which can reduce the hindrance of Coulomb repulsion for the migration of lithium ions and achieve an increase in ionic conductivity.
[0083] When preparing the doped halide solid electrolyte, adjusting mx + my + z < 1 can generate more A vacancies, which can reduce the hindrance of Coulomb repulsion for the migration of lithium ions and achieve an increase in ionic conductivity.
[0084] The incorporated C ions can regulate the lithium ion content and induce the generation of more lithium vacancies. In addition, by adjusting the content of C ions, the doped halide solid electrolyte can have the same phase and space group as the original matrix material.
[0085] m is a coefficient for adjusting the lithium-deficient state and lithium-rich state. 0 < m < 1.5. By adjusting the value of m, the lithium content of the doped halide solid electrolyte can be adjusted to achieve the regulation between the lithium-deficient state (i.e., high lithium ion vacancy number) and the lithium-rich state (i.e., high lithium ion concentration). The lithium ion vacancy number and lithium ion concentration are two important factors affecting the ionic conductivity of the doped halide solid electrolyte, but these two factors are antagonistic to each other. Different all-solid-state batteries have different requirements for the doped halide solid electrolyte. Therefore, by adjusting the value of m, the doped halide solid electrolyte can be switched between the lithium-deficient state and the lithium-rich state, its structural design is more free, and the battery application is more extensive.
[0086] In the embodiments of the present application, the above-mentioned doped halide solid electrolyte is prepared by a method combining grinding and annealing, which can effectively achieve the uniformity of doping and the stability of the structure, thereby enabling the smoothness of the ion migration channel and obtaining a doped halide solid electrolyte with high ionic conductivity.
[0087] In some embodiments, the rotation speed of grinding can be 300 rpm - 600 rpm, for example, it can be 300 rpm, 325 rpm, 350 rpm, 375 rpm, 400 rpm, 425 rpm, 450 rpm, 475 rpm, 500 rpm, 525 rpm, 550 rpm, 575 rpm, 600 rpm, or a range composed of any of the above values.
[0088] Optionally, the rotation speed of grinding can be 400 rpm - 550 rpm.
[0089] In some embodiments, the grinding time can be 6 h - 72 h, for example, it can be 6 h, 8 h, 10 h, 16 h, 22 h, 28 h, 34 h, 40 h, 48 h, 56 h, 64 h, 72 h, or a range composed of any of the above values.
[0090] Optionally, the grinding time can be 12 h - 48 h.
[0091] In some embodiments, the grinding can be ball milling. Optionally, manual grinding can also be performed before ball milling. Optionally, the manual grinding time can be 10 min - 30 min.
[0092] In some embodiments, the annealing temperature can be 100°C - 300°C, for example, it can be 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, or a range composed of any of the above values.
[0093] Optionally, the annealing temperature can be 100°C - 200°C.
[0094] In some embodiments, the annealing time may be 2 h-24 h, for example, 2 h, 5 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, or a range consisting of any of the above values.
[0095] Optionally, the annealing time may be 5h-12h.
[0096] By adjusting the grinding parameters and annealing parameters, the doped halide solid electrolyte can have a higher ionic conductivity.
[0097] Optionally, the shielding gas may include argon.
[0098] A battery cell includes a positive electrode, a negative electrode, and an electrolyte layer.
[0099] The positive electrode includes a positive electrode active material and a doped halide solid electrolyte provided in an embodiment of the present application.
[0100] The doped halide solid electrolyte provided in the embodiment of the present application has better ionic conductivity performance than the original matrix material, and can improve the problem of poor solid-solid interface contact, thereby being beneficial to the electrochemical performance of the all-solid-state battery, so that it has a high first coulombic efficiency and good cycle stability.
[0101] Compared with sulfide solid electrolytes, the doped halide solid electrolyte provided in the embodiments of the present application has good positive electrode stability and can also be matched with high-voltage positive electrode active materials to further improve the energy density of all-solid-state batteries.
[0102] Optionally, the mass ratio of the positive electrode active material to the doped halide solid electrolyte can be 90:10 to 70:30, for example, 90:10, 88:12, 86:14, 84:16, 82:18, 80:20, 78:22, 76:24, 74:26, 72:28, 70:30, or a range consisting of any of the above numerical values.
[0103] Optionally, the positive electrode active material may include one or more of lithium cobalt oxide and its modified materials, lithium iron phosphate and its modified materials, lithium manganese iron phosphate and its modified materials, lithium nickel cobalt manganese oxide and its modified materials, lithium nickel cobalt aluminum oxide and its modified materials, lithium nickel oxide and its modified materials, lithium manganese oxide and its modified materials, lithium titanate, sulfur, selenium, and tellurium. The modified materials of the above-mentioned positive electrode active materials may be doping modification and / or surface coating modification of the positive electrode active materials.
[0104] As an example, the positive electrode active material may include but is not limited to LiCoO 2 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (abbreviated as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O 2 (abbreviated as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (abbreviated as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (abbreviated as NCM811), LiNi 0.96 Co 0.02 Mn 0.02 O 2 (abbreviated as Ni96), LiNi 0.80 Co 0.15 Al 0.05 O 2 、LiFePO 4 , and one or more of their respective modified materials.
[0105] The positive electrode further includes a positive electrode conductive agent. As an example, the positive electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and vapor-grown carbon fiber (VGCF).
[0106] The positive electrode can be prepared by a dry method, for example, the positive electrode active material, the positive electrode conductive agent, etc. can be formed by pressing, or it can be prepared by a wet method.
[0107] The positive electrode may include a positive electrode binder or may not include a positive electrode binder, which can be adjusted according to the preparation process of the positive electrode and the battery cell.
[0108] In some embodiments, the positive electrode includes a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene oxide, fluorinated acrylic resin, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). One or more.
[0109] The positive electrode may include a positive electrode current collector or may not include a positive electrode current collector. In some embodiments, the positive electrode includes a positive electrode current collector, and the positive electrode active material and the doped halide solid electrolyte are located on at least one surface of the positive electrode current collector. The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0110] The negative electrode includes a negative electrode active material, which may include one or more of graphite, graphene, carbon nanotubes, mesophase microcarbon beads, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, metal oxides, metallic lithium, lithium alloys, and lithium composite materials.
[0111] Silicon-based materials may include one or more of elemental silicon, silicon oxide, silicon carbide, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin compounds, and tin alloys. Metal oxides include TiO 2 、MoO 2 、In 2 O 3 、Al 2 O 3 , Cu 2 O.VO 2 , Ga 2 O 3 , Sb 2 O 5 、Bi 2 O 5Other elements in the lithium alloy may include one or more elements of In, Mg, Al, Zn, Sn, Ag, Au, Ga, Pt, and Fe, for example, Li-In alloy, Li-Mg alloy, Li-Al alloy, Li-Zn alloy, Li-Fe alloy, etc.
[0112] The negative electrode may be a metal sheet, such as a lithium sheet, a lithium alloy sheet, etc., and may also be prepared by a dry method, such as forming the negative electrode active material by pressing, or may be prepared by a wet method.
[0113] In some embodiments, the negative electrode may further include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include but is not limited to one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0114] In some embodiments, the negative electrode may further include a negative electrode binder. As an example, the negative electrode binder may include, butadiene styrene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). One or more.
[0115] The negative electrode may include or may not include a negative electrode current collector. In some embodiments, the negative electrode includes a negative electrode current collector, and the negative electrode active material is located on at least one surface of the negative electrode current collector. The negative electrode current collector may include a metal foil, a three-dimensional porous current collector, or a composite current collector. As examples of metal foils, copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil may be used. As examples of three-dimensional porous current collectors, copper mesh, nickel mesh, aluminum mesh, foam copper, foam nickel, and foam aluminum may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0116] The electrolyte layer includes a solid electrolyte material. The solid electrolyte material includes one or more of a sulfide solid electrolyte and a halide solid electrolyte. Optionally, the solid electrolyte material includes a sulfide solid electrolyte.
[0117] The battery cell can be prepared by methods known in the art, for example, the assembly methods of the battery cell include but are not limited to button cells, molded batteries, square shell batteries, soft pack batteries, etc. In some embodiments, the preparation method of the battery cell includes the following steps: grinding the doped halide solid electrolyte, the positive electrode active material, and the positive electrode conductive agent to obtain a positive electrode powder; adding the solid electrolyte used to form the electrolyte layer to the model battery, and performing a first cold pressing treatment; adding the positive electrode powder to one side of the model battery, and performing a second cold pressing treatment; adding the negative electrode to the other side of the model battery, and performing a third cold pressing treatment, so as to obtain the battery cell.
[0118] Electrical devices
[0119] The present application also provides an electrical device, which includes a battery provided in the present application. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0120] The electrical device can select the type of all-solid-state battery according to its usage requirements, such as battery cells, battery modules or battery packs.
[0121] like Figure 6 As shown, as an example, the electric device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0122] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0123] Example
[0124] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0125] Example 1
[0126] Doped halide solid electrolyte is Li 2 Zr 0.9 Nb 0.08 Cl 6 .
[0127] The raw materials that meet the expected stoichiometric ratio are 84.78 mg LiCl, 209.74 mg ZrCl 4 and 21.61 mg NbCl 5 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0128] Example 2
[0129] Doped halide solid electrolyte is Li 1.97 Zr 0.9 Nb 0.08 Ce 0.01 Cl 6 .
[0130] The raw materials that meet the expected stoichiometric ratio are 83.51 mg LiCl, 209.74 mg ZrCl 4 、21.61mg NbCl 5 and 2.46 mg CeCl 3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0131] Example 3
[0132] Doped halide solid electrolyte is Li 2 Zr 0.8 Nb 0.16 Cl 6 .
[0133] The raw materials that meet the expected stoichiometric ratio are 84.78 mg LiCl, 186.43 mg ZrCl 4 and 43.22 mg NbCl 5 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0134] Example 4
[0135] Doped halide solid electrolyte is Li 1.97 Zr 0.8 Nb 0.16 Ce 0.01 Cl 6 .
[0136] The raw materials that meet the expected stoichiometric ratio are 83.51 mg LiCl, 186.43 mg ZrCl 4 、43.22mg NbCl 5 and 2.46 mg CeCl 3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0137] Example 5
[0138] Doped halide solid electrolyte is Li 2.77 Zr 0.64 Nb 0.128 Ce 0.01 Cl 6 .
[0139] The raw materials that meet the expected stoichiometric ratio are 117.42 mg LiCl, 149.15 mg ZrCl 4 、34.58mg NbCl 5 and 2.46 mg CeCl 3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0140] Example 6
[0141] Doped halide solid electrolyte is Li 1.97 Zr 0.8 Ta 0.16 La 0.01 Cl 6 .
[0142] The raw materials that meet the expected stoichiometric ratio are 83.51 mg LiCl, 186.43 mg ZrCl 4 、57.31mg TaCl 5 and 2.45 mg LaCl 3After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0143] Comparative Example 1
[0144] Doped halide solid electrolyte is Li 2 ZrCl 6 .
[0145] The raw materials, 84.78 mg LiCl and 233.04 mg ZrCl, which meet the expected stoichiometric ratio, are added. 4 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0146] Comparative Example 2
[0147] Doped halide solid electrolyte is Li 1.9 Zr 0.9 Nb 0.1 Cl 6 .
[0148] The raw materials that meet the expected stoichiometric ratio are 80.54 mg LiCl, 209.74 mg ZrCl 4 and 27.02 mg NbCl 5 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0149] Example 7
[0150] Doped halide solid electrolyte is Li 2.98 Y 0.8 Zr 0.15 Ca 0.01 Cl 6 .
[0151] The raw materials that meet the expected stoichiometric ratio are 126.32 mg LiCl and 156.21 mg YCl 3 、34.96mg ZrCl 4 and 1.11 mg CaCl 2After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0152] Comparative Example 3
[0153] Doped halide solid electrolyte is Li 3 YC 6 .
[0154] The raw materials, 127.17 mg LiCl and 195.26 mg YCl, which meet the expected stoichiometric ratio, are added. 3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0155] Comparative Example 4
[0156] Doped halide solid electrolyte is Li 2.8 Y 0.8 Zr 0.2 Cl 6 .
[0157] The raw materials that meet the expected stoichiometric ratio are 118.69 mg LiCl, 156.21 mg YCl 3 and 46.61 mg ZrCl 4 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0158] Example 8
[0159] Doped halide solid electrolyte is Li 2.97 In 0.8 Nb 0.12 La 0.01 Cl 6 .
[0160] The raw materials that meet the expected stoichiometric ratio are 125.90 mg LiCl, 176.94 mg InCl 3 、32.42mg NbCl 5 and 2.45 mg LaCl 3After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0161] Comparative Example 5
[0162] Doped halide solid electrolyte is Li 3 InCl 6 .
[0163] The raw materials, 127.17 mg LiCl and 221.18 mg InCl, which meet the expected stoichiometric ratio, are added. 3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0164] Comparative Example 6
[0165] Doped halide solid electrolyte is Li 2.6 In 0.8 Nb 0.2 Cl 6 .
[0166] The raw materials that meet the expected stoichiometric ratio are 110.21 mg LiCl, 176.94 mg InCl 3 and 54.03 mg NbCl 5 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0167] Comparative Example 7
[0168] Using commercial sulfide solid electrolyte Li 6 PS 5 Cl (Macklin).
[0169] Testing of doped halide solid electrolytes
[0170] Ionic conductivity test: 100 mg of the above solid electrolyte was added to the model battery, pressed and assembled into a lithium-indium symmetrical battery, and then the ionic conductivity of the prepared solid electrolyte was tested using electrochemical impedance spectroscopy (EIS) on the autolab workstation. The test frequency range was 0.1 Hz to 10 6Hz. The ionic conductivity of the solid electrolyte is calculated based on the impedance value and the Arrhenius formula. Crystal form test: XRD test is performed on the above solid electrolyte powder sample using an X-ray diffractometer to qualitatively confirm whether the crystal phase of the solid electrolyte changes before and after doping. The test range is 10°-90°, the scanning speed is 3° / min, and the test is protected by argon atmosphere throughout. The test instrument is a Bruker D8 X-ray diffractometer.
[0171] The product was tested by XPS, and after the test, the XPS data was analyzed and processed using Thermo Scientific™ Avantage. The test instrument was Thermo ESCALAB 250XI X-ray Photoelectron Spectrometer.
[0172] Table 1
[0173]
[0174] The doped halide solid electrolytes prepared in Examples 1 to 6 are Li 2 ZrCl 6 The doped halide solid electrolyte prepared in Example 7 is obtained by doping on the basis of Li 3 YC 6 The doped halide solid electrolyte prepared in Example 8 is obtained by doping on the basis of Li 3 InCl 6 It is obtained by doping on the basis of. Through XRD testing, the diffraction peaks of the halide solid electrolyte before and after doping can be compared, thereby confirming that the phase state and space group of the original matrix material are not affected after doping, and fine-tuning based on the structure of the original matrix material is achieved. By monitoring the characteristic XPS signal peaks of different elements, the elemental composition of the doped halide solid electrolyte after doping can be determined, and it can be confirmed that the doping has been successfully achieved. After the doped halide solid electrolyte sample is digested with nitric acid, the element content ratio in the sample can be confirmed by ICP-OES (inductively coupled plasma emission spectrometer), and it can be confirmed that the synthesis of the target stoichiometric ratio doped halide solid electrolyte has been successfully achieved.
[0175] It can be seen from the above test results that the doped halide solid electrolyte prepared in the embodiment of the present application has significantly improved ionic conductivity compared with the undoped halide solid electrolyte matrix material.
[0176] It can be seen from the above test results that the doped halide solid electrolyte prepared in the embodiment of the present application has higher ionic conductivity than the conventionally doped halide solid electrolyte.
[0177] It can be seen from the above test results that the doping strategy provided in the embodiments of the present application can be applied to doped halide solid electrolytes of different matrix types.
[0178] It can be seen from the test results of Example 1 and Example 2 that the C ions doped into the original matrix material and the ionic radius of the C ions is made larger than the ionic radius of the A ions and the ionic radius of the B ions. The C ions can play a role in widening the distance between the cation layers and weakening the resistance to lithium ion migration. This can make the prepared doped halide solid electrolyte have higher ionic conductivity, and can also make the prepared all-solid-state battery have high capacity, high first coulomb efficiency and good cycle stability.
[0179] Next, the solid-state electrolyte prepared above is assembled into an all-solid-state battery, and its effect on the performance of the all-solid-state battery is tested.
[0180] The assembly of all-solid-state batteries is based on the model battery. The inner diameter of the model battery is 10 mm.
[0181] Positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O 2 The above solid electrolyte and vapor-grown carbon fiber (VGCF) have a mass ratio of 70:28:2 and a surface capacity of 3 mAh / cm 2 .
[0182] Electrolyte layer: 100 mg commercial sulfide solid electrolyte Li 6 PS 5 Cl (Macklin).
[0183] Negative electrode: lithium indium alloy.
[0184] Testing of all-solid-state batteries
[0185] The test was conducted on the Blue Power Battery Test System. The test temperature was 25°C and the charge and discharge voltage range was 2.6V-4.3V.
[0186] The 0.1C discharge specific capacity test method is as follows: the all-solid-state battery is fully charged and fully discharged at a 0.1C rate, and the ratio of the first discharge capacity to the mass of the positive electrode active material is taken as the 0.1C discharge specific capacity.
[0187] The 0.33C discharge specific capacity test method is as follows: the all-solid-state battery is fully charged and fully discharged at a 0.33C rate, and the ratio of the first discharge capacity to the mass of the positive electrode active material is taken as the 0.33C discharge specific capacity.
[0188] The test method for the first coulombic efficiency is as follows: the all-solid-state battery is fully charged and discharged at a rate of 0.1C, and the ratio of the first discharge capacity to the first charge capacity is taken as the first coulombic efficiency.
[0189] The cycle performance test method is as follows: After the all-solid-state battery is cycled three times at a rate of 0.1C, it is cycled 200 times at a rate of 0.33C. The capacity retention rate after 200 cycles = the discharge capacity after 200 cycles at 0.33C / the discharge capacity after the first cycle at 0.33C.
[0190] Table 2
[0191]
[0192] It can be seen from the above test results that the doped halide solid electrolyte prepared in the embodiment of the present application can enable the all-solid-state battery to have high capacity, high first coulombic efficiency and good cycle stability compared with the undoped halide solid electrolyte matrix material.
[0193] It can be seen from the above test results that the doped halide solid electrolyte prepared in the embodiment of the present application has a higher room for improvement in ion conductivity compared with conventionally doped halide solid electrolytes, and thus can be better suitable for all-solid-state batteries.
[0194] It can be seen from the test results of Example 1 and Example 2 that by doping C ions and making the ionic radius of the C ions larger than the ionic radius of the A ions and larger than the ionic radius of the B ions, the C ions can widen the distance between the cation layers and weaken the resistance to lithium ion migration, thereby making the prepared doped halide solid electrolyte have higher ionic conductivity, and can also make the prepared all-solid-state battery have high capacity, high first coulomb efficiency and good cycle stability.
[0195] Example 2-1
[0196] Doped halide solid electrolyte is Li 1.97 Zr 0.8 Nb 0.16 Ce 0.01 Cl 6 .
[0197] The raw materials that meet the expected stoichiometric ratio are 83.51 mg LiCl, 186.43 mg ZrCl 4 、43.22mg NbCl 5 and 2.46 mg CeCl 3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 6 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0198] Example 2-2
[0199] Doped halide solid electrolyte is Li 1.97 Zr 0.8 Nb 0.16 Ce 0.01 Cl 6 .
[0200] The raw materials that meet the expected stoichiometric ratio are 83.51 mg LiCl, 186.43 mg ZrCl 4 、43.22mg NbCl 5 and 2.46 mg CeCl 3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 600 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0201] Example 2-3
[0202] Doped halide solid electrolyte is Li 1.97 Zr 0.8 Nb 0.16 Ce 0.01 Cl 6 .
[0203] The raw materials that meet the expected stoichiometric ratio are 83.51 mg LiCl, 186.43 mg ZrCl 4 、43.22mg NbCl 5 and 2.46 mg CeCl 3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 200 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0204] Embodiment 2-4
[0205] Doped halide solid electrolyte is Li 1.97 Zr 0.8 Nb 0.16 Ce 0.01 Cl 6 .
[0206] The raw materials that meet the expected stoichiometric ratio are 83.51 mg LiCl, 186.43 mg ZrCl 4 、43.22mg NbCl 5 and 2.46 mg CeCl3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 300 °C in an argon atmosphere for 6 h to obtain a doped halide solid electrolyte.
[0207] Embodiment 2-5
[0208] Doped halide solid electrolyte is Li 1.97 Zr 0.8 Nb 0.16 Ce 0.01 Cl 6 .
[0209] The raw materials that meet the expected stoichiometric ratio are 83.51 mg LiCl, 186.43 mg ZrCl 4 、43.22mg NbCl 5 and 2.46 mg CeCl 3 After uniform mixing and manual grinding for 20 min, the mixture was transferred to a ball mill and ball-milled at 400 rpm for 12 h in an argon atmosphere. The ground material was then transferred to a muffle furnace and annealed at 100 °C in an argon atmosphere for 12 h to obtain a doped halide solid electrolyte.
[0210] Table 3
[0211]
[0212] It can be seen from the above test results that by further adjusting the grinding parameters and annealing parameters, the doped halide solid electrolyte can have a higher ionic conductivity.
[0213] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and the same effect as the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A doped halide solid electrolyte for an all-solid-state battery, characterized in that: The general formula of the doped halide solid electrolyte is Li 6-ma-cz A a+ mx B b+ my C c+ z X6, a is the valence of ion A, b is the valence of ion B, c is the valence of ion C, a is 3 or 4, b is 4 or 5, c is 2 or 3, ax+by=a, b>a, x>y>0, 0 <z≤0.2,0.5≤m≤1.25,mx+my+z<1,0.8≤mx<1; A includes one or more of In, Y, and Zr, B includes one or more of Ti, Zr, Hf, V, Nb, and Ta, C includes one or more of Ca, La, Ce, Pr, Nd, Sm, Eu, and Gd, the ionic radius of C ions is greater than the ionic radius of A ions, the ionic radius of C ions is greater than the ionic radius of B ions, and A, B, and C are different; X includes one or more of halogens.
2. The doped halide solid electrolyte according to claim 1, characterized in that: a is 4 and b is 5.
3. The doped halide solid electrolyte according to claim 1, characterized in that: The doped halide solid electrolyte satisfies at least one of the following conditions (1) to (3): (1) B includes one or more of Zr, Nb and Ta; (2) C includes one or more of Ca, La, and Ce, and A, B, and C are different; (3) X includes one or more of Cl, Br, and I.
4. The doped halide solid electrolyte according to claim 1, characterized in that: The doped halide solid electrolyte satisfies at least one of the following conditions (1) to (3): (1) The doped halide solid electrolyte is in any one of a glass phase, a glass-ceramic phase, and a crystalline phase; (2) The volume distribution particle size Dv50 of the doped halide solid electrolyte is 0.5 μm-10 μm; (3) The ionic conductivity of the doped halide solid electrolyte at 25° C. is 0.5 mS / cm-15 mS / cm.
5. A method for preparing a doped halide solid electrolyte, characterized in that: The steps include: The halide of element Li, the halide of element A, the halide of element B, and the halide of element C are uniformly mixed in proportion, and then ground under a protective gas atmosphere, and then the ground materials are annealed under a protective gas atmosphere to obtain a doped halide solid electrolyte. The general formula of the doped halide solid electrolyte is Li 6-ma-cz A a+ mx B b+ my C c+ z X6, a is the valence of ion A, b is the valence of ion B, c is the valence of ion C, a is 3 or 4, b is 4 or 5, c is 2 or 3, ax+by=a, b>a, x>y>0, 0 <z≤0.2,0.5≤m≤1.25,mx+my+z<1,0.8≤mx<1; A includes one or more of In, Y, and Zr, B includes one or more of Ti, Zr, Hf, V, Nb, and Ta, C includes one or more of Ca, La, Ce, Pr, Nd, Sm, Eu, and Gd, the ionic radius of C ions is greater than the ionic radius of A ions, the ionic radius of C ions is greater than the ionic radius of B ions, and A, B, and C are different; X includes one or more of halogens.
6. The preparation method according to claim 5, characterized in that: The preparation method satisfies at least one of the following conditions (1) to (4): (1) The grinding speed is 300rpm-600rpm; (2) The grinding time is 6h-72h; (3) Annealing temperature is 100℃-300℃; (4) Annealing time is 2h-24h.
7. The preparation method according to any one of claims 5 to 6, characterized in that: The preparation method satisfies at least one of the following conditions (1) to (4): (1) The grinding speed is 400rpm-550rpm; (2) The grinding time is 12h-48h; (3) Annealing temperature is 100℃-200℃; (4) Annealing time is 5h-12h.
8. An all-solid-state battery, comprising a positive electrode, characterized in that: The positive electrode comprises a positive electrode active material and the doped halide solid electrolyte according to any one of claims 1 to 4 or the doped halide solid electrolyte prepared by the preparation method according to any one of claims 5 to 7.
9. The all-solid-state battery according to claim 8, characterized in that: The mass ratio of the positive electrode active material to the doped halide solid electrolyte is 90:10 to 70:
30.
10. The all-solid-state battery according to claim 8, characterized in that: The positive electrode active material includes one or more of lithium cobalt oxide and its modified materials, lithium iron phosphate and its modified materials, lithium manganese iron phosphate and its modified materials, lithium nickel cobalt manganese oxide and its modified materials, lithium nickel cobalt aluminum oxide and its modified materials, lithium nickel oxide and its modified materials, lithium manganese oxide and its modified materials, lithium titanate, sulfur, selenium, and tellurium.
11. The all-solid-state battery according to any one of claims 8 to 10, characterized in that: The all-solid-state battery also includes a negative electrode and an electrolyte layer, the electrolyte layer is located between the positive electrode and the negative electrode, and the negative electrode includes one or more of graphite, graphene, carbon nanotubes, intermediate phase microcarbon beads, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, metal oxides, metallic lithium, lithium alloys, and lithium composite materials.
12. An electrical device, characterized in that: Including the all-solid-state battery as described in any one of claims 8-11.
